Hubungan Usia, Jenis Kelamin, Dan Faktor Pendidikan Terhadap Kualitas Hidup Anak Penderita Kanker Yang Menjalani Kemoterapi - Saputri, Diah Ayu; Wahyudi, Totok; Musta'in, Musta'in (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Cancer is one of the non-communicable diseases that is still a serious health problem and a cause of death in the world. The prevalence of cancer in children in Indonesia is 4%, this is one of the major problems of children's health in Indonesia. Chemotherapy treatment has a physiological and psychological impact which can later cause problems that can have an impact on the quality of life of children. This study aims to determine the relationship between age, gender, and education factors on the quality of life of children with cancer during chemotherapy at Dr. Moewardi Hospital Surakarta. This study used a descriptive method with a cross sectional design. The sample in the study was a child with cancer who underwent chemotherapy. Sampling was done using the consecutive sampling method with a total of 50 respondents. The measuring tool uses the PedsQL 4.0 quality of life questionnaire.The results of the research that have been conducted by statistical tests obtained a sig value of 0.036 (p<0.05) and a positive correlation test of 0.298 between age and quality of life, gender is not related to quality of life, education level is not related to quality of life. It can be concluded that there is a weak relationship between age and the quality of life of children with cancer during chemotherapy.